2011
DOI: 10.2105/ajph.2011.300335
|View full text |Cite
|
Sign up to set email alerts
|

Transforming the Delivery of Care in the Post–Health Reform Era: What Role Will Community Health Workers Play?

Abstract: The Patient Protection and Affordable Care Act (PPACA) affords opportunities to sustain the role of community health workers (CHWs). Among myriad strategies encouraged by PPACA are prevention and care coordination, particularly for chronic diseases, chief drivers of increased health care costs. Prevention and care coordination are functions that have been performed by CHWs for decades, particularly among underserved populations. The two key delivery models promoted in the PPACA are accountable care organizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
75
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(75 citation statements)
references
References 29 publications
0
75
0
Order By: Relevance
“…Efforts to clarify the role that CHWs will have in the delivery of health care services, including legislative and policy efforts for CHW certification, continue to be debated [26]. Team climate can act as a mediator on patient care outcomes [27], and it may impact the innovativeness and ability of health care teams and organizations to adopt new ways of delivering health care [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Efforts to clarify the role that CHWs will have in the delivery of health care services, including legislative and policy efforts for CHW certification, continue to be debated [26]. Team climate can act as a mediator on patient care outcomes [27], and it may impact the innovativeness and ability of health care teams and organizations to adopt new ways of delivering health care [28].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research on team climate has shown it is affected by a variety of internal and external factors not assessed in this study including: leadership, electronic health record capability, organizational culture, organizational tenure, support from new roles, and professional role conflicts [31][32]. In addition, the survey questions did not address potential mediating and moderating variables including: payment options available for CHW services [26], team training, and organizational resources available for innovation and adoption of new models of health care delivery.…”
Section: Limitationsmentioning
confidence: 94%
“…21,24,44,45 Finally, because of the focus of CHW interventions on primary health care, health promotion and disease prevention, these interventions have demonstrated both actual and potential control of high costs of medical services and inappropriate use of emergency services when and if CHWs and their interventions are integrated into health care systems. [46][47][48] …”
Section: Evaluation Studiesmentioning
confidence: 99%
“…The health insurance mandate under the Affordable Care Act introduces opportunities for currently uninsured hypertensive individuals to afford and enroll in health insurance. 38 Additionally, the American Heart Association recommends that states and certain localities develop surveillance capacity that would include direct the assessment of "awareness, detection, treatment, and control of obesity, hypertension, dyslipidemia, and diabetes." 29 Although requiring extensive efforts, community organizing is one type of approach to reach a large community-based population in order to provide mechanisms for individuals to access necessary healthcare resources for hypertension management.…”
Section: Controlmentioning
confidence: 99%